2014
DOI: 10.1136/bmjspcare-2014-000694
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic enzyme replacement therapy (PERT) for malabsorption in patients with metastatic pancreatic cancer

Abstract: Guidelines recommending empiric treatment of PERT in patients with metastatic PC are not currently being utilised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 20 publications
(20 reference statements)
1
36
0
3
Order By: Relevance
“…This was confirmed in a survey conducted on members of the Dutch and German patient associations for pancreatic disorders, that clearly showed that most patients suffering from PEI after pancreatic surgery are undertreated even in countries with well-organized health care systems [41]. In an Australian retrospective study on 129 patients with metastatic pancreatic cancer and symptoms that could be attributable to malabsorption, only 21% patients were prescribed PERT [42]. Another study highlighted a clear clinical gap in managing PEI in patients with supportive care for pancreatic cancer [43].…”
Section: Pancreatic Enzyme Replacement Therapy (Pert)mentioning
confidence: 88%
“…This was confirmed in a survey conducted on members of the Dutch and German patient associations for pancreatic disorders, that clearly showed that most patients suffering from PEI after pancreatic surgery are undertreated even in countries with well-organized health care systems [41]. In an Australian retrospective study on 129 patients with metastatic pancreatic cancer and symptoms that could be attributable to malabsorption, only 21% patients were prescribed PERT [42]. Another study highlighted a clear clinical gap in managing PEI in patients with supportive care for pancreatic cancer [43].…”
Section: Pancreatic Enzyme Replacement Therapy (Pert)mentioning
confidence: 88%
“…Despite these benefits, evidence suggests that clinicians are not initiating treatment often enough, nor replacing enzymes adequately. A recent study showed that only 21% of patients with pancreatic cancer received PERT, despite 70% reporting symptoms consistent with fat maldigestion[ 28 ]. A Northern European cross sectional survey of patients receiving PERT found 68% had steatorrhoea and 39% had weight loss.…”
Section: Management Of Pancreatic Exocrine Insufficiencymentioning
confidence: 99%
“…In addition, PERT was associated with significant improvement in fat and protein digestion in patients with a partial/total pancreatic resection [ 28 ]. Of note, a recent study reported low rates of PERT prescription (21%) in patients with metastatic pancreatic cancer, in which the vast majority of patients had tumors of the pancreatic head and were likely to have had a blocked pancreatic duct [ 29 ].…”
Section: Introductionmentioning
confidence: 99%